'Anāshir Su - Faiq Ilham Rosyadi (Universitas Islam Negeri Palangka Raya, 2020)
Learning difficulties can be interpreted as obstacles in the learning process to achieve learning goals. This obstacle can be caused by several factors. This research study is a quantitative descriptive study that aims to find out the factors that cause learning difficulties of students in class XI on nahwu shorof lesson. The study used a total sampling in which, all students of class XI with a total of 40 students were taken. Data collection techniques used research instruments in the form of questionnaires. The instrument validity to be used were content validity and construct validity, while the Cronbach alpha formula was used to test the reliability. Data analysis in this study used descriptive statistical analysis techniques. The results showed that the factors of learning difficulties experienced by students in the nahwu-shorof subject in terms of internal factors were the cognitive abilities and student learning habits, while in terms of external factors are the school factor.The cognitive ability factor is limited to the level of students' understanding of the materials being studied. In the study habits of students seen from the routine of learning and repeating the materials that have been explained by the teacher. While the school factor is seen in terms of the atmosphere of learning in schools and learning facilities.